INDONESIAN-ENGLISH CODE SWITCHING IN THE NOVEL TEST PACK BY NINIT YUNITA - Rani Puri Hendriyani, - (2012)
This study entitled Indonesian-English Code Switching in the Novel Test Pack by Ninit Yunita, aims to investigate the differences of the types and the functions of code switching between male and female characters in the novel. The present study is a descriptive study. 163 code switching in the novel were analyzed by using a theory proposed by Poplack (1980) for investigating the types of code switching and Poplack (1980) and Koziol (2000) for reviewing the functions of code switching. The findings show that there are three types of code switching used by both male and female characters in the novel, namely Tag switching, Intrasentential switching, and Intersentential switching. Intrasentential switching becomes the most dominant types used by both characters with 63%, followed by Intersentential switching with 31%, and Tag switching with 6%. Furthermore, in terms of the function of code switching, there are twelve functions used by both male and female characters in the novel. Expressive becomes the most dominant function used by female character with 16 occurrences while Designation and Emphasis become the most dominant function used by male character with 6 occurrences for each. So, it can be seems that female tend to be more talkative than male, female tend to be more sensitive than male when using emotional terms such as happy, romantic and missing, and both of male and female characters in the novel show their emotion (anger) frequently.